Initial Development and Psychometric Evidence of Physical Education Grit Scale (PE-Grit) - Guelmami, Noomen; Chalghaf, Nasr; Tannoubi, Amayra; Puce, Luca; Azaiez, Fairouz; Bragazzi, Nicola Luigi (Frontiers in Public Health, 2022)
Backgrounds:Grit is a key concept in positive psychology and educational science. The concept measures two related constructs that are interest and effort. Several instruments have been developed to measure the construct in professional and educational contexts, but no tools have been developed with specific contexts such as physical education and sport in consideration. Aims: To develop and test a measurement scale to assess Grit in the context of physical education and sports. Methods: Two exploratory (phase 1) and confirmatory (phase 2) samples administered the 16-item Arabic language scale the PH-GRIT. In addition, the confirmatory sample additionally administered the R-SPQ-2F Two-Factor Learning Approaches Scale.The factor structure was examined initially by exploratory factor analysis on the first sample and subsequently by confirmatory factor analysis on the second sample. The reliability test was performed by checking the internal consistency simultaneously by the three indices:McDonald's ω, Cronbach’s α,and Gutmann’s λ6.Concurrent validity was checked by Pearson's correlation between the PH-GRIT and the two dimensions of SPQ-2R.The results:After exploratory factor analysis, which made it possible to identify the factors and preliminary validate the designed instrument, confirmatory factor analysis was carried out on 3 second-order and hierarchical models to be able to identify the most suitable model.A third-order hierarchical model with two physical and academic components, each formed by interest and effort presented the best fit indices: chi X2 = 192.95 (p <0.01), and the X2 / DF = 1.36; GFI = 0.97; AGFI = 0.97; CFI = 0.99; TLI = 0.99; RMSEA = 0.025. Besides, the McDonald's ω, internal consistency, and the Gutmann’s λ6 index varied between 0.79 and 0.85 for the four dimensions of the scale.Conclusion: The PH-GRIT scale exhibits adequate factor structure, good reliability, and acceptable concurrency and can be administered to assess Grit among physical education and sports students.